Modeling Hematological Diseases and Cancer With Patient-Specific Induced Pluripotent Stem Cells - Kim, Huensuk; Schaniel, Christoph (Frontiers in Immunology, 2018)
The advent of induced pluripotent stem cells (iPSCs) together with recent advances in genome editing, microphysiological systems, tissue engineering and xenograft models present new opportunities for the investigation of hematological diseases and cancer in a patient-specific context. Here we review the progress in the field and discuss the advantages, limitations and challenges of iPSC-based malignancy modeling. We will also discuss the use of iPSCs and its derivatives as cellular sources for drug target identification, drug development and evaluation of pharmacological responses.